PLCG2 promotes hepatocyte proliferation in vitro via NF-κB and ERK pathway by targeting bcl2, myc and ccnd1 - Donghui Ma; Fang Lian; Xiaobai Wang (Artificial Cells, Nanomedicine, and Biotechnology)
Phospholipase Cγ2 (PLCG2) has been implicated in the regulation of cell proliferation, transformation, and tumor growth. In this study, we investigate the mechanism of PLCG2 action using a short interference RNA (siRNA) method. The effects of PLCG2 on rat liver BRL-3A cells treated siRNA were studied by 3-(4,5-dimethyl-2-thiazolyl)-2,5-diphenyl-2-H-tetrazolium bromide (MTT assay), bromodeoxyuridine (BrdU) labelling assay, flow cytometry method (FCM), quantitative real-time polymerase chain reaction (qRT-PCR) and western blot. The results showed when PLCG2 was reduced, cell vitality and proliferation rate were significantly decreased (p < .05 vs. control). FCM analysis showed that the number of cell division phase (G2 + M) was declined (p < .05 vs. control). RT-PCR and western blot revealed that the expression of signalling related genes NF-κB, FOS, JUN and ELK, target genes BCL2, CCNB1 and CCND1 were remarkably down-regulated in cells treated with PLCG2 siRNAs. Based on these results, we conclude PLCG2 plays an important role in rat liver cell proliferation via ERK and NF-κB pathway by regulating the expression of BCl2, MYC and CCND1.